2016
DOI: 10.1002/cdq.12059
|View full text |Cite
|
Sign up to set email alerts
|

Career Barriers for Chinese Immigrants in the United States

Abstract: To assist career counselors working with diverse populations, this article examines the career barriers experienced by Chinese immigrants in the United States. It begins with an overview of the history and background of Chinese immigrants. The rest of the article is based on an adapted ecological model for studying career barriers for Chinese immigrants that is an integration of Bogardus's (1933) social distance theory and Bronfenbrenner's (1977Bronfenbrenner's ( , 1979 ecological systems theory of human devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…This is an issue which has not just been witnessed within United Kingdom workplace but has in fact been mirrored widely across Europe, where globalmigration has seen those classed as "non-elite" speakers (Gal, 2006, p. 165) being judged by an idealised standard of language. This is also mirrored reported through the lens of language discrimination within the USA (Thorpe-Lopez, 2007;Leong and Tang, 2016;Taylor et al, 2019) as well as Australia (Kosny et al, 2017).…”
Section: Identity and Otheringsupporting
confidence: 73%
“…This is an issue which has not just been witnessed within United Kingdom workplace but has in fact been mirrored widely across Europe, where globalmigration has seen those classed as "non-elite" speakers (Gal, 2006, p. 165) being judged by an idealised standard of language. This is also mirrored reported through the lens of language discrimination within the USA (Thorpe-Lopez, 2007;Leong and Tang, 2016;Taylor et al, 2019) as well as Australia (Kosny et al, 2017).…”
Section: Identity and Otheringsupporting
confidence: 73%
“…Conflicts in career beliefs and career choices and decisions are largely affecting career development of individuals in different collectivistic Chinese societies (Kwan, 2009). For Chinese populations in Western host societies such as the United States and Canada, because a relatively complete career service system is basically established, their major career barrier might be how to adapt at different levels, such as work environment, communities, schools, and families, with increasing language ability and improving social support (Chen & Hong, 2016;Leong & Tang, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The article by Leong and Tang (2016) reviews career barriers experienced by Chinese immigrants in the United States. The article by Leong and Tang (2016) reviews career barriers experienced by Chinese immigrants in the United States.…”
Section: Content Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, other study found that working hours, interpersonal relationships at work, training, and economy had an important influence on participants’ well-being [ 11 ]. Finally, another study identified that career barriers among Chinese immigrants are related to ethnic stereotypes to language, lack of social support, and workplace discrimination [ 12 ].…”
Section: Introductionmentioning
confidence: 99%